Evaluation of the Health Service Management System in Controlling Environmental Risk Factors for Tuberculosis - Achmad Rifai (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Tuberculosis (TB) remains a major health issue in Indonesia, closely linked to environmental risk factors such as poor ventilation and inadequate sanitation. Objective: To evaluate the health service management system in controlling environmental risk factors for TB at Hutabaginda Health Center, North Tapanuli District. Research Methods: This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and document studies, and analyzed using thematic analysis with data triangulation. Results: Although policies for controlling environmental risk factors exist, their implementation faces challenges, including limited trained human resources, inadequate sanitation facilities, weak supervision, and suboptimal coordination with local government. These obstacles reduce the effectiveness of environmental-based TB control programs. Conclusion: The health service management system at Hutabaginda Health Center has not been optimal in controlling environmental risk factors for TB. Strengthening healthcare worker training, improving infrastructure, enhancing internal supervision, and intensifying coordination with local government are essential to improve TB control effectiveness.